Physical Sciences: Astrophysical Portals are a Source of New Knowledge - Antonov, A. A. (European Journal of Applied Sciences, 2025)
The article claims that the version of the special theory of relativity studied in all physics textbooks is incorrect and sets out the main provisions of its corrected version. And from the relativistic formulas of the corrected version of SRT it follows that in nature, in addition to our visible universe, there are mutually invisible universes and anti-universes that are connected to each other by a large number of portals. At the same time, the entrances to the portals are supposedly the so-called anomalous zones, which people avoid visiting, since it is very difficult to get out of them. However, scientific research of portals by unmanned robotic complexes is possible and necessary. Such scientific research will allow solving a number of very important scientific problems - proving the existence of mutually invisible universes adjacent to our visible universe, explaining the Fermi paradox, proving the possibility of traveling not only in the space of the hidden Multiverse, but also in time, etc.